Development of the Peripartum Cardiomyopathy Quality Of Life Registry - Rosman, Lindsey (East Carolina University, 2016)
Peripartum cardiomyopathy (PPCM) is a relatively rare form of heart failure that develops in young women in the third trimester of pregnancy or during the postpartum period. Despite its potentially devastating impact on new mothers and their families, no prior studies have evaluated the extent to which PPCM and its treatment negatively affect survivors' long-term physical health and emotional recovery. The current study sought to develop a prospective online research registry to examine clinically relevant behavioral and psychosocial outcomes in women with PPCM. A conceptual model was also developed and used to evaluate predictors of depression. Seventy-five PPCM patients (mean age of 35.0 years, SD = 5.8 years) enrolled in the registry. Among PPCM patients in this sample, 35% endorsed symptoms of clinical depression which was associated with worse adherence to scheduled medical appointments. More than half the women in this cohort (52%) endorsed clinical levels of generalized anxiety. High levels of cardiac anxiety, good maternal social support, poor adherence to heart failure self-care behaviors and reproductive risk behaviors were also found. Finally, multivariate analyses revealed that physical health significantly predicted depression (p = 0.004). The addition of generalized anxiety and disease-specific distress to the regression model significantly increased R2 (p [less than] 0.001) and explained an additional 38.1% of the variation in depression. Demographic factors and disease severity were not significantly associated with depression. In sum, data from this study support the prevalence and persistence of adverse behavioral and psychosocial outcomes in women with PPCM. Further research, assessment and intervention is warranted to facilitate patient education and improve patient care.
Keywords: Peripartum cardiomyopathy; Heart failure; Puerperium--Physiological aspects; Puerperium--Psychological aspects; Myocardium--Diseases--Psychological aspects